If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z + -74 = 0 Reorder the terms: -74 + z = 0 Solving -74 + z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '74' to each side of the equation. -74 + 74 + z = 0 + 74 Combine like terms: -74 + 74 = 0 0 + z = 0 + 74 z = 0 + 74 Combine like terms: 0 + 74 = 74 z = 74 Simplifying z = 74
| 102/200 | | f-19= | | 5r+6-2r=7r-19 | | -10=y+14 | | 4y(5x-y)= | | X/8=x-63 | | 24+c= | | 10x+15y=1390 | | 9(x+6)-3=51 | | (4x^2y^8)(-3x^3y)= | | 33+x=49 | | -30-(-65)-29-4= | | X^2-64=9 | | 3x^7+5x^3=1000000000000000 | | 4b*7=x | | 9=-3(21-y)+2(y-4) | | -32t=0 | | 9(x+3)+4=11x-2(x-5) | | 16t^2=0 | | 7+h=-12 | | -6p+8+7p=17 | | 9x+16=6x+4+4x-2 | | 17.9-x=12.8 | | 413=7(-7x-18) | | 4u-13=51 | | 8x/9-6=58 | | a+(-6)= | | 4+9=c^2 | | 12x=19.2 | | Cos(2x+10)=sin(3x-30) | | -7(-10x-5)=455 | | 18-x+24=56 |